2021
DOI: 10.1111/1475-6773.13870
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for sustaining high‐quality pediatric asthma care in community hospitals

Abstract: Objective: To identify strategies associated with sustained guideline adherence and high-quality pediatric asthma care in community hospitals. Data sources: Primary qualitative data from clinicians in hospitals across the United States (collected December 2019-February 2021).Study design: Pathways for Improving Pediatric Asthma Care (PIPA) was a national quality improvement (QI) intervention. In a prior quantitative study, data from 23 community hospitals in PIPA were analyzed to identify sites with the highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In total, 25 studies (reported in 27 papers due to 2 companion reports) met the final inclusion criteria for the review (Fig. 1 ) [ 51 77 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In total, 25 studies (reported in 27 papers due to 2 companion reports) met the final inclusion criteria for the review (Fig. 1 ) [ 51 77 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The 25 included studies reported on 16 health disciplines. Most studies focused on the adult population ( n = 16) [ 51 , 55 57 , 59 , 61 , 62 , 64 , 66 71 , 73 , 74 ], while fewer had a pediatric focus ( n = 8) [ 53 , 58 , 60 , 63 , 65 , 72 , 75 , 77 ], and one reported on the neonatal intensive care unit [ 76 ]. Thirteen of the included studies took place in acute care [ 55 , 57 , 60 – 62 , 66 , 68 , 69 , 71 , 73 , 75 77 ], 11 in tertiary care [ 51 , 53 , 56 , 58 , 59 , 63 – 65 , 70 , 72 , 74 ], and 1 in ambulatory care [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…EMR) can help your organization meet its goals, and developing a plan to collect and reassess data going forward [43,44]. Sustainability of these interventions can pose a challenge, but may rely on creating accountability for roles/responsibilities, the availability of champions advocating use of the intervention and having adequate support/resources at the organizational level [45 ▪▪ ].…”
Section: Challenges With Practical Implementationmentioning
confidence: 99%